Review of the earthworm fauna of Iran with emphasis on Kohgiluyeh & Boyer-Ahmad Province - Farhadi, Zeinab; Malek, Masoumeh; Elahi, Elahe (Zootaxa, 2013)
Earthworms were collected in forests, damp habitats, springs, orchards and agricultural fields of the Kohgiluyeh & Boyer Ahmad Province, Iran, from April 2009 to April 2010. Specimens were collected at 20 established stations by digging and by diluted formalin methods. Ten species belonging to family Lumbricidae were identified based on morphology: Apor-rectodea caliginosa (Savigny, 1826), Ap. rosea (Savigny, 1826), Ap. jassyensis (Michaelsen, 1891), Dendrobaena veneta (Rosa, 1886), D. byblica (Rosa, 1893) complex, D. orientalis orientalis Černosvitov 1940, Eisenia fetida (Savigny, 1826), Eiseniella tetraedra (Savigny, 1826), Octolasion lacteum (Örley, 1881), Perelia kaznakovi (Michaelsen, 1910). Ap. calig-inosa was the dominant species in this province and D. orientalis orientalis is a new record for Iran. A checklist of all earthworms species form Iran is presented, containing 19 species. Then, in order to show earthworm geographical affini-ties, hierarchical analysis were applied to available data on earthworm of Iran.